Roles of physical fields in the extraction of pectin from plant food wastes and byproducts: A systematic review. (February 2023) - Ling, Bo; Ramaswamy, Hosahalli S.; Lyng, James G.; Gao, Jilong; Wang, Shaojin
Graphical abstract: Highlights: Physical field assisted extraction (PFAE) of pectin from plant source was reviewed. Electromagnetic fields with microwave and radio frequency energy results in accelerated pectin extraction (PE). Acoustic, electric, and mechanical fields also enhance PE through non-thermal effects. Combination of PFAE contributes to boost pectin yields and physicochemical qualities. Upscaling studies are needed for PE industrial applications through physical fields. Abstract: Pectin is a naturally occurring hydrocolloid found in the cell wall and middle lamella of many plants and has numerous functional applications in food and other related industries. The type of extraction methods used in production has a strong influence on the structural or physicochemical properties of the resultant pectin and the potential application or market value of the produced pectin. Many conventional extraction methods are well-established and commercially well adopted. However, the increased demand for pectin due to limitations of the existing methods in terms of efficiency and influence on end product quality has been renewed in developing novel techniques or procedures that help to alleviate these problems. In this review paper, a series of strategies involving the application of physical fields, such as acoustic, electromagnetic, electric and mechanical one, are reviewed for potential opportunities to improve the yield and quality attributes of pectin extracted from plant food wastes and byproducts. The extraction mechanism, processing equipment, key operating parameters as well as advantages and disadvantages of each method are systematically reviewed, and findings and conclusions on the potential applications of each method are described. Moreover, the challenges and future directions of physical field assisted extraction (PFAE) of pectin are also discussed to facilitate a better understanding of the complex mechanism in PFAE and optimizing operational parameters. This review may also provide specific theoretical information and practical applications to improve the design and scale up PFAE of pectin.